Hydrogen-Rich Saline Inhibits NLRP3 Inflammasome Activation and Attenuates Experimental Acute Pancreatitis in Mice - Ren, Jian-Dong; Ma, Jie; Hou, Jun; Xiao, Wen-Jin; Jin, Wei-Hua; Wu, Juan; Fan, Kai-Hua (Mediators of Inflammation, 2014)
Increasing evidence has demonstrated that reactive oxygen species (ROS) induces oxidative stress and plays a crucial role in the pathogenesis of acute pancreatitis (AP). Hydrogen-rich saline (HRS), a well-known ROS scavenger, has been shown to possess therapeutic benefit on AP in many animal experiments. Recent findings have indicated that the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome, an intracellular multiprotein complex required for the maturation of interleukin- (IL-) 1β, may probably be a potential target of HRS in the treatment of AP. Therefore, in this study, we evaluated the activation of NLRP3 inflammasome and meanwhile assessed the degree of oxidative stress and inflammatory cascades, as well as the histological alterations in mice suffering from cerulein-induced AP after the treatment of HRS. The results showed that the activation of NLRP3 inflammasome in AP mice was substantially inhibited following the administration of HRS, which was paralleled with the decreased NF-κB activity and cytokines production, attenuated oxidative stress and the amelioration of pancreatic tissue damage. In conclusion, our study has, for the first time, revealed that inhibition of the activation of NLRP3 inflammasome probably contributed to the therapeutic potential of HRS in AP.